THE MODULE «VIRTUAL ELECTRONIC BOARD» OF DISTANCE LEARNING SYSTEM «KHERSON VIRTUAL UNIVERSITY 2.0» (Journal of Information Technologies in Education (ITE), 2010)
Results of structure modeling, construction of learning model and development of program module Whiteboard – a virtual electronic board of distance learning system «Kherson Virtual University» are presented.
Keywords: a virtual electronic board; distance learning system; program module Whiteboard